Letter from Fritz Boas to Georg Bredig - Boas, Fritz (1938)
Fritz Boas, the Berlin-based immigration attorney for Max Bredig (1902-1977), informs Georg Bredig (1868-1944) that his son's motorcycle was sold.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Emigration and immigration; Motorcycles